Rancang Bangun Aplikasi Keamanan Data Menggunakan Metode AES Pada Smartphone - Hasibuan, Amir Mahmud (MEANS (Media Informasi Analisa dan Sistem), 2017)
Cryptography is one technique used to improve the security aspects of information. Cryptography is the study of science and art to maintain a message or data information so that the data is safe. Cryptography supports the needs of two aspects of information security, namely secrecy (protection of the confidentiality of information data) and authenticity (protection against counterfeiting and changing unwanted information). Along with the development of computer technology, the world of information technology requires a stronger and safer cryptographic algorithm. Currently the Advanced Encryption Standard (AES) is used as the latest standard cryptographic algorithm. For this reason, it is necessary to prepare an application that can secure a data and maintain its confidentiality so that it is not known by unauthorized parties. One alternative that can be used in making a data security application is by applying the Advanced Encryption Standard (AES) algorithm. hence the design of a data security application on a smartphone by designing the application of encryption and description of text data using the AES method. This method does a round of 10 rounds to get the results of encryption and decryption in the text.